2013
DOI: 10.1063/1.4826936
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic production of single micrometer-sized hydrogel beads utilizing droplet dissolution in a polar solvent

Abstract: In this study, a microfluidic process is proposed for preparing monodisperse micrometer-sized hydrogel beads. This process utilizes non-equilibrium aqueous droplets formed in a polar organic solvent. The water-in-oil droplets of the hydrogel precursor rapidly shrunk owing to the dissolution of water molecules into the continuous phase. The shrunken and condensed droplets were then gelled, resulting in the formation of hydrogel microbeads with sizes significantly smaller than the initial droplet size. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 63 publications
(63 reference statements)
0
32
0
Order By: Relevance
“…We recently developed a process to produce monodisperse, single micrometer-sized particles made of natural/synthetic polymers by using droplets in a nonequilibrium state formed in microfluidic devices 35,36 . This process begins by forming droplets of an aqueous solution of precursor molecules in a continuous phase of water-soluble polar organic solvent, such as methyl acetate.…”
Section: Introductionmentioning
confidence: 99%
“…We recently developed a process to produce monodisperse, single micrometer-sized particles made of natural/synthetic polymers by using droplets in a nonequilibrium state formed in microfluidic devices 35,36 . This process begins by forming droplets of an aqueous solution of precursor molecules in a continuous phase of water-soluble polar organic solvent, such as methyl acetate.…”
Section: Introductionmentioning
confidence: 99%
“…As an efficient strategy to produce general microparticles with small sizes, a solvent extraction method was developed and utilized to produce various types of particles (Freitas , 2005). Several studies have been reported on the microfluidic production of alginate particles by employing this concept (Rondeau and Cooper-White, 2008;Sugaya et al, 2013), wherein a polar organic solvent (e.g., dimethyl carbonate and methyl acetate) that is miscible with water was used as the continuous phase. Sugaya et al (2013) prepared single micrometer-sized alginate microparticles via the rapid dissolution of microdroplets in a non-equilibrium state (Figure 6).…”
Section: Particle Production Using Miscible Water-oil Two Phase Owsmentioning
confidence: 99%
“…Several studies have been reported on the microfluidic production of alginate particles by employing this concept (Rondeau and Cooper-White, 2008;Sugaya et al, 2013), wherein a polar organic solvent (e.g., dimethyl carbonate and methyl acetate) that is miscible with water was used as the continuous phase. Sugaya et al (2013) prepared single micrometer-sized alginate microparticles via the rapid dissolution of microdroplets in a non-equilibrium state (Figure 6). Droplets of a diluted solution of Na-alg were generated in the continuous phase of methyl acetate.…”
Section: Particle Production Using Miscible Water-oil Two Phase Owsmentioning
confidence: 99%
“…We recently reported strategies for producing monodisperse microparticles by using microfluidic droplets in a non-equilibrium state (i.e., non-equilibrium droplets) 29,30 . Oil-in-water (O/W) or water-in-oil (W/O) droplets were generated by using water and a polar organic solvent (e.g., ethyl acetate) as either the continuous or dispersed phase.…”
Section: Introductionmentioning
confidence: 99%